Let’s be Frank: a re-examination of the Lochlea crannog bit in a Continental contex - Maguire, Rena (Proceedings of the Society of Antiquaries of Scotland, 2024)
A unique bridle bit found at Lochlea crannog, South Ayrshire appears to show a fusion of traditional local Iron Age technology with Continental early medieval styling, specifically the influence of Frankish horsemanship (hereafter equitation) and equipment (hereafter lorinery and tack). The re-examination of the Lochlea bit allows consideration of Scotland’s connections to early medieval Francia as well as highlighting the archaeological potential of the artefacts found at Lochlea, with emphasis on a modern examination of the chronology of the site.